Kitainik axioms do not characterize the class of inclusion measures based on contrapositive fuzzy implications - Madrid-Labrador, Nicolás Miguel; Cornelis, Chris (Elsevier, 2022)
In this short communication, we refute the conjecture by Fodor and Yager from [5] that the class of inclusion measures proposed by Kitainik coincides with that of inclusion measures based on contrapositive fuzzy implications. In particular, we show that the conjecture only holds when the considered universe of discourse is finite.
Keywords: Matemáticas difusas; Kitainik axioms; Fuzzy inclusion; Fuzzy implications